2019
DOI: 10.1038/s41598-019-49388-3
|View full text |Cite
|
Sign up to set email alerts
|

Active behaviour during early development shapes glucocorticoid reactivity

Abstract: Glucocorticoids are the final effectors of the stress axis, with numerous targets in the central nervous system and the periphery. They are essential for adaptation, yet currently it is unclear how early life events program the glucocorticoid response to stress. Here we provide evidence that involuntary swimming at early developmental stages can reconfigure the cortisol response to homotypic and heterotypic stress in larval zebrafish ( Danio rerio ), also reducing startle reactivity and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Zebrafish are emerging as an excellent model system for experimental studies of stress-induced developmental programming [9][10][11][12][13][14][15][16][17][18]. We recently showed that zebrafish embryos treated chronically with 1 μM cortisol develop into adults that maintain elevated whole body cortisol levels and aberrantly express pro-inflammatory genes, with higher basal expression levels in peripheral tissues but a blunted response to tailfin injury or lipopolysaccharide injection [13], indicating that the treatment has long-term effects on the neuroendocrine stress axis and GC-regulated gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish are emerging as an excellent model system for experimental studies of stress-induced developmental programming [9][10][11][12][13][14][15][16][17][18]. We recently showed that zebrafish embryos treated chronically with 1 μM cortisol develop into adults that maintain elevated whole body cortisol levels and aberrantly express pro-inflammatory genes, with higher basal expression levels in peripheral tissues but a blunted response to tailfin injury or lipopolysaccharide injection [13], indicating that the treatment has long-term effects on the neuroendocrine stress axis and GC-regulated gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Early-Life Stress Impairs CM Proliferation First, to examine whether the cardiac developmental program is affected by brainmediated stress triggered by a physical challenge experienced during early life, we exposed 4-dpf zebrafish larvae to a vibrational stimulus causing water shaking for 16 h ( Figure 1A). This type of stimulus was previously employed to model a brain-mediated stress response in zebrafish larvae (Castillo-Ramírez et al, 2019). Interestingly, following this short-term exposure to the stressor, we observed a reduction of CM proliferation.…”
Section: Resultsmentioning
confidence: 79%
“…This finding suggests the opposite observation to that of restrained larvae: maintenance of an expanded progenitor pool at the expense of neuronal differentiation. In another study, an involuntary swim paradigm resulted in dysregulation of the HPA axis (Castillo-Ramírez et al, 2019). Here, in a later larval stage, animals that had experienced involuntary swimming during early development reconfigure their cortisol response to homotypic and heterotypic stressors.…”
Section: Water Movementmentioning
confidence: 91%
“…Other tools that can be used as stress sensors are also available in fish, such as transgenic lines that can detect stressors that alter motor function (Shahid et al, 2016) or alter glucocorticoid (GC) signalling (Weger et al, 2013;Krug et al, 2014), and behavioural assays to identify HPI axis modifiers in the rapid time domain (Lee et al, 2019). Larval zebrafish are known to alter their behaviour in response to an acute stressor (De Marco et al, 2013Lopez-Luna et al, 2017;Lee et al, 2019) and following exposure to a physical stimulus (Castillo-Ramírez et al, 2019). Zebrafish larvae display a variety of behaviours that can be quantified (Kalueff et al, 2013;De Marco et al, 2014Groneberg et al, 2015;Karpenko et al, 2020) and exhibit social behaviour (Engeszer et al, 2007;Dreosti et al, 2015;Groneberg et al, 2020), some of which can be modulated by stressor exposure (Eachus et al, 2017;Shen et al, 2020).…”
Section: The Stress Response In Zebrafishmentioning
confidence: 99%